Sarcoidosis in iron-steel industry: mini case series - Üzmezoğlu, Bilge; Şimşek, Cebrail; Gülgösteren, Sevtap; Gebeşoğlu, Berna; Sarı, Gülden; Çelik, Deniz (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Sarcoidosis is a disease of unknown etiology. Despite the proposed connection between the development of sarcoidosis and exposure to environmental and toxic substances, no definitive associations could be established. Also, the role of silica and silicates in the etiology of this condition is currently unknown. Heat-treatment of silica results in the generation of tridymite and cristobalite forms and iron-steel industry represents one branch of industry in which silicone element is exposed to temperatures around 2000ºC. Studies reporting on the incidence of sarcoidosis in the workers of iron-steel industry are scarce in number, and workers of this industrial branch are known to be exposed to silica in the form of cristobalite, nano-particulate silicone, metal oxides, and silicates. These substances, which have respiratory toxic properties and have been reported to be associated with autoimmune conditions, may also play a role in the pathogenesis of sarcoidosis. In our clinic, sarcoidosis was diagnosed in a total of 4 individuals, who works in the iron-steel industry. Through this report involving a series of patients with sarcoidosis, we also wanted to discuss the role of crystalline silica forms and silicates in the etiology of sarcoidosis, which is also considered to be an auto-immune condition.